Inclusive disaster risk management (DRM) for Bertam valley community - Sabri Muda, Rahsidi; Tukiman, Izawati; Mohd. Hussain, Mohd. Ramzi; Zen, Ismawi (Malaysian Institute of Planners, 2018)
This paper focuses on the inclusiveness of Disaster Risk Management. The study assesses proactive adaptation of Early Warning System (EWS) for Disaster Risk Reduction Program in Bertam Valley. The study aims to identify community preferences as an initiative to improve the effectiveness of the EWS system. In order to sustain the awareness and preparedness of EWS, continuous involvement by the community is necessary to make them resilient. Specific focus is given to Person with Disabilities (PwDs), elderly and children. Therefore, it is vital to understand the efficient methods to alarm PwDs, elderly and children during emergencies occurrence, which will focus on the implementation of types of alarm in EWS with regards to the early warning alarm and emergency notification. The finding from this paper is useful to assist local authorities and emergency responder in the formulation of warning and evacuation procedures to save the PwDs if dam failure is imminent.